Macromedia Flash Multimedia as an Effort to Improve Students' Critical Thinking Skills in Islamic Education Learning at SMP Negeri 4 Meulaboh - Sanusi, Imam; Pratama, Diky Safrial (Jurnal Profesi Guru Indonesia, 2025)
This study aims to determine the influence of the use of multimedia Macromedia Flash on students' critical thinking skills in learning Islamic Religious Education at SMP Negeri 4 Meulaboh. The research method used is Class Action Research (PTK) which is carried out in two cycles. The research subjects consisted of 30 students in grade VIII. The data collection instruments are in the form of critical thinking skills tests and observation sheets for student and teacher activities. The results of the study showed an increase in students' critical thinking skills after the application of Macromedia Flash multimedia. In the initial condition, only 40% of students reached the category of good critical thinking, then increased to 70% in cycle I, and reached 90% in cycle II. In addition, student activeness in learning has also increased significantly. The conclusion of this study is that the use of multimedia Macromedia Flash is effective in improving students' critical thinking skills in learning Islamic Religious Education. These findings make an important contribution to the development of multimedia-based learning strategies that can improve the quality of religious education at the junior high school level.